Kebolehan Bahasa Masyarakat Cina Peranakan Kelantan - Mohd Nor, Mohd Roslan; Hasan, Haryati (Jurnal Usuluddin, 2010)
Peranakan Chinese in Kelantan have a long history of interaction with the Malay community, especially the Kelantan Malay community who live either in urban or rural areas. History of the formation of the Peranakan Chinese of Kelantan dated back many years, mainly through marriage, trade and others even prior to 18th century. Although the process of integration and cultural assimilation occurred, but the Kelantan Peranakan Chinese community continue their lives as Chinese. Mixing with the Malays of Kelantan has affected them from various aspects, including the aspect of language. Most of the languages used by Kelantan Peranakan Chinese were affected by the Kelantan dialect. Hence, this paper discusses the ability of the language spoken by the Peranakan Chinese of Kelantan which include Hokkien, Bahasa Melayu and the ability to speak Thai, all of these in dialect of Kelantan.